2008
DOI: 10.1007/s00436-008-1005-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of leaf extracts of Vitex negundo L. (Family: Verbenaceae) against larvae of Culex tritaeniorhynchus and repellent activity on adult vector mosquitoes

Abstract: Petroleum ether (60-80 degrees C) extracts of the leaves of Vitex negundo (Verbenaceae) were evaluated for larvicidal activity against larval stages of Culex tritaeniorhynchus in the laboratory. Larvae of C. tritaeniorhynchus were found more susceptible, with LC(50) and LC(90) values of 2.4883 and 5.1883 mg/l, respectively. Human volunteers wearing special terricot (68:32) fabrics, in the form of armbands, anklets, headbands, collar, and shoulder and pocket strips impregnated with V. negundo leaf extract were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 12 publications
0
49
0
1
Order By: Relevance
“…aegypti, Anopheles stephensi and Culex quinquefasciatus [7] . Petroleum ether extracts of Vitex negundo leaves offered 8 h of bite protection (2 mg/cm 2 ) by different mosquito species in the field [24,25] . A patented extract of the seeds of Vitex agnus castus was shown effective against mosquitoes resulting in more than 6 h protection against Culex quinquefasciatus and Anopheles stephensi, and 3-4 h against Ae.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti, Anopheles stephensi and Culex quinquefasciatus [7] . Petroleum ether extracts of Vitex negundo leaves offered 8 h of bite protection (2 mg/cm 2 ) by different mosquito species in the field [24,25] . A patented extract of the seeds of Vitex agnus castus was shown effective against mosquitoes resulting in more than 6 h protection against Culex quinquefasciatus and Anopheles stephensi, and 3-4 h against Ae.…”
Section: Discussionmentioning
confidence: 99%
“…quinquefasciatus, and their LC 50 values were 2 214.7 and 5 362.6 ppm, respectively [38] . Mullai and Jebanesan [39] [41] reported that the petroleum ether (60-80 曟) extracts of the leaves of V. negundo were evaluated for larvicidal activity against larval stages of Cx. tritaeniorhynchus in the laboratory with LC 50 and LC 90 values of 2.488 3 and 5.188 3 mg/L, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable international interest in developing benign natural products as an alternative to harmful synthetic pesticides to control invertebrate pests of medical and economic importance [2,3] . Botanical phytochemicals with mosquitocidal potential are now recognized as potent alternative insecticides to replace synthetic insecticides in mosquito control programs due to their excellent larvicidal, pupicidal and adulticidal properties [4][5][6][7][8] . Phytochemicals are less environmentally harmful than synthetic agrochemicals.…”
Section: Introductionmentioning
confidence: 99%